An evaluation of the enamel surface after debonding, polishing and application of the different remineralizing agents a scanning electron microscopic study - Vahdani, Vahid
Abstract:The purpose of this in vitro study were to evaluate the enamel surface structure subjected to various debonding techniques, clean-up procedures for residual adhesive removal and final polishing procedure with pumice and rubber cup. In addition, the ability of two commercially-available remineralizing agents to inhibit demineralization and promote remineralization was also assessed. Othodontic brackets were bonded to fifty six (56) experimental teeth using Ormco Blugloo light-cured adhesive material. Enamel surface structures were examined with a scanning electron microscope at X 30 and X 200 magnifications. Subsequent to debonding, clean-up and polishing procedures the SEM photomicrographs were assessed using Adhesive Remnants Index (ARI) and Enamel Surface Index (ESI). In order to assess the ability of the two commercially available remineralizing agents in inhibiting demineralization and promoting remineralization, the SEM photomicrographs were qualitatively assessed by means of the Energy Dispersive X-ray Analysis (EDX). A non-parametric statistical method using STATA software was utilized for Stages 2 and 3. A Fisher Exact Test was used to determine the difference in proportion among the three different clean-up techniques and the conditions of enamel surface. At the fourth stage, a comparison between the control and the test sections was done using Mann-Whiteny U test and between test immediately after application and after 48 hours of the same treatment, a Wilcoxon sign-rank test was utilized.